ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS BUNG HATTA UNTUK BERWIRAUSAHA - Daniati Puttri; Nailal Husna (Jurnal Apresiasi Ekonomi, 2016)
This research was conducted at the Faculty of Economics, University of Bung Hatta Padang. The population included all students of S1 of Economics Faculty in Bung Hatta University who have completed the enterpreuneurship course in uneven semester 2015/2016. The sampling method used was convenience sampling that samples were close by and can be found easily that appropriate to this study, it has acquired as many as 150 respondents. Results of hypothesis testing were a family background did not affect the intentions Faculty of Economics University of Bung Hatta to entrepreneurship. While personality traits significantly influence to the entrepreneurial intentions on the students of the Economics Faculty in Bung Hatta University. Key Words: Family Background, Marks of Personality and Entrepreneurship Intention